The concurrent upshot of optical path-length and pressure on O3 absorption cross-section in relation to green communication - Michael David; Patrick Enenche; Caroline O. Alenoghena; Mohd Haniff Ibrahim; Sevia M. Idrus; Tay Ching En Marcus (International Journal of Advances in Applied Sciences, 2022)
Ozone gas is a greenhouse gas. Accurate measurement of its concentration is dependent on the right value of the ozone gas absorption cross-section. In the literature, discrepancies and inconsistencies have been however linked with ozone gas absorption cross-section. In the literature, information on the pressure effect on pressures less than 100 mbar and greater than 100 but less than 1000 mbar is not available for the visible spectrum. Thus, creating an information gap that this manuscript is intended to fill up. This is the problem that has been addressed in this present work. The method of simulation with SpectralCalc is the method adopted for the present work. HITRAN 2012 simulator, available on spectralcalc.com, was used in simulating the ozone gas absorption cross-section to determine the simultaneous effect of optical path length and pressure at two peak wavelengths in the visible spectrum. Simulation outcomes were obtained for an optical path length of 10 cm to 120 cm showing that the optimum absorption cross-section value of 5.1084×10-25 m2/molecule at 603 nm and 4.7182×10-25 m2/molecule at 575 nm for gas cells length between 10 cm and 120 cm are obtained at peak points. Pressure values at which ozone gas absorption cross-section becomes a constant value of 5.1058×10-25 m2/molecule at 603 nm and 4.7158×10-25 m2/molecule at 575 nm is optical path length dependent. The percentage difference between 5.1084×10-25 m2/molecule and 5.1058×10-25 m2/molecule is 0.05% for all lengths of gas cells considered. Similarly, the percentage difference between 4.7182×10-25 m2/molecule and 4.7158×10-25 m2/molecule is also 0.05% for all lengths of gas cells considered. These results are relevant for high-accuracy and high-precision ozone gas measurements. Furthermore, efficient measurement of ozone gas is a direct enhancement of green communication.